Quantitative microbial risk assessment of bioaerosol emissions from squat and bidet toilets during flushing - Ali, Wajid; Hu, Zhen; Tang, Zhe‐ren; Liu, Si‐yi; Nasir, Zaheer A.; Coulon, Frederic; Liu, Peng; Yan, Cheng (Wiley, 2025)
Bioaerosol emissions during toilet flushing are an often‐overlooked source of potential health risks in shared public facilities. This study systematically investigated the emission characteristics of Staphylococcus aureus and Escherichia coli bioaerosols in washrooms with squat and bidet toilets under varying flushing conditions and ventilation scenarios. Using Monte Carlo simulation–based quantitative microbial risk assessment and sensitivity analysis, the study estimated the disease burden and identified key factors influencing risk. The results showed that squat toilets generated 1.7–2.6 times higher concentrations of S. aureus bioaerosols and 1.2–1.4 times higher concentrations of E. coli bioaerosols compared to bidet toilets. After the first flush, bioaerosol concentrations were 1.3–1.8 times (S. aureus) and 1.2–1.4 times (E. coli) lower than those observed after the second flush. The second flush released a higher proportion of fine bioaerosol particles (<4.7 µm), increasing inhalation risks. The disease health risk burden was consistently one order of magnitude lower after the first flush than the second one. Ventilation with a turned‐on exhaust fan further reduced the risk by one order of magnitude. Sensitivity analysis identified exposure concentration as the most influential parameter, contributing up to 50% of the overall risk. This study highlights the importance of optimizing toilet design and ventilation systems to mitigate bioaerosol emissions and associated health risks. It provides actionable insights for improving public washroom hygiene and minimizing bioaerosol exposure.
Keywords: Strategic, Defence & Security Studies; bioaerosol; disease burden; Monte Carlo simulation; quantitative microbial risk assessment; sensitivity analysis; toilet